Neighborhood walkability and 12-year changes in cardio-metabolic risk: the mediating role of physical activity - Manoj Chandrabose; Ester Cerin; Suzanne Mavoa; David Dunstan; Alison Carver; Gavin Turrell; Neville Owen; Billie Giles-Corti; Takemi Sugiyama (BMC, 2019)
Abstract Background Living in walkable neighborhoods may provide long-term cardio-metabolic health benefits to residents. Little empirical research has examined the behavioral mechanisms in this relationship. In this longitudinal study, we examined the potential mediating role of physical activity (baseline and 12-year change) in the relationships of neighborhood walkability with 12-year changes in cardio-metabolic risk markers. Methods The Australian Diabetes, Obesity and Lifestyle study collected data from adults, initially aged 25+ years, in 1999-2000, 2004-05, and 2011-12. We used 12-year follow-up data from 2023 participants who did not change their address during the study period. Outcomes were 12-year changes in waist circumference, weight, systolic and diastolic blood pressure, fasting and 2-h postload plasma glucose, high-density lipoprotein cholesterol, and triglycerides. A walkability index was calculated, using dwelling density, intersection density, and destination density, within 1 km street-network buffers around participants' homes. Spatial data for calculating these measures were sourced around the second follow-up period. Physical activity was assessed by self-reported time spent in moderate-to-vigorous physical activity (including walking). Multilevel models, adjusting for potential confounders, were used to examine the total and indirect relationships. The joint-significance test was used to assess mediation. Results There was evidence for relationships of higher walkability with smaller increases in weight (P = 0.020), systolic blood pressure (P < 0.001), and high-density lipoprotein cholesterol (P = 0.002); and, for relationships of higher walkability with higher baseline physical activity (P = 0.020), which, in turn, related to smaller increases in waist circumference (P = 0.006), weight (P = 0.020), and a greater increase in high-density lipoprotein cholesterol (P = 0.005). There was no evidence for a relationship of a higher walkability with a change in physical activity during the study period (P = 0.590). Conclusions Our mediation analysis has shown that the protective effects of walkable neighborhoods against obesity risk may be in part attributable to higher baseline physical activity levels. However, there was no evidence of mediation by increases in physical activity during the study period. Further research is needed to understand other behavioral pathways between walkability and cardio-metabolic health, and to investigate any effects of changes in walkability.